2011
DOI: 10.1016/j.ajpath.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of β-Thalassemia Shows a Liver-Specific Down-Regulation of Abcc6 Expression

Abstract: ␤-Thalassemia and pseudoxanthoma elasticum (PXE) are distinct genetic disorders. Yet, a dystrophic mineralization phenotype similar to PXE has frequently been associated with ␤-thalassemia or sickle cell anemia patients of Mediterranean descent. These calcifications are clinically and structurally identical to inherited PXE. As we previously excluded the presence of PXE-causing mutations in the ABCC6 gene of ␤-thalassemia patients with PXE manifestations, we hypothesized that a molecular mechanism independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
(78 reference statements)
1
36
0
1
Order By: Relevance
“…ABCC6 is an organic anion transporter primarily present in the basolateral plasma membrane of hepatocytes (Pomozi et al, 2013). ABCC6 deficiency is linked to several mineralization pathologies: pseudoxanthoma elasticum (PXE, OMIM 264800) is characterized by late onset and progressive calcifications in the skin leading to prominent dermal manifestations as well as in vascular and ocular tissues (Le Saux et al, 2000); β-thalassemia (OMIM 187550), which may be related to reduced levels of ABCC6 protein in the liver (Martin et al, 2011); and a subset of generalized arterial calcification of infancy (GACI, OMIM 208000), that is typically associated with ENPP1 mutations and results in early patient mortality (Nitschke et al, 2012). In several inbred strains of mice, including C3H/HeJ, ABCC6 deficiency causes an acute calcification phenotype affecting the myocardium and the media of large arteries (Aherrahrou et al, 2008; Doehring et al, 2006; Meng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ABCC6 is an organic anion transporter primarily present in the basolateral plasma membrane of hepatocytes (Pomozi et al, 2013). ABCC6 deficiency is linked to several mineralization pathologies: pseudoxanthoma elasticum (PXE, OMIM 264800) is characterized by late onset and progressive calcifications in the skin leading to prominent dermal manifestations as well as in vascular and ocular tissues (Le Saux et al, 2000); β-thalassemia (OMIM 187550), which may be related to reduced levels of ABCC6 protein in the liver (Martin et al, 2011); and a subset of generalized arterial calcification of infancy (GACI, OMIM 208000), that is typically associated with ENPP1 mutations and results in early patient mortality (Nitschke et al, 2012). In several inbred strains of mice, including C3H/HeJ, ABCC6 deficiency causes an acute calcification phenotype affecting the myocardium and the media of large arteries (Aherrahrou et al, 2008; Doehring et al, 2006; Meng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A PXE phenotype without mutations in ABCC6 has frequently been associated with β-thalassemia patients [7]. A β-thalassemia mouse model showed a significant decrease in ABCC6 protein expression, even if it occurs too late in life and is thus insufficient to promote mineralization [8]. Generalized arterial calcification of infancy (GACI) is a hereditary disorder generally associated with mutations in the ecto-nucleotide pyrophosphatase/phosphodiesterase type I (Enpp1) gene [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, these patients were devoid of known PXE-causing mutations [60], and the genetic basis governing clinical findings in β-thalassemia and inherited PXE, therefore, appears distinct. It was recently demonstrated that a β-thalassemia mouse model displayed downregulated Abcc6 protein liver expression [61]. This finding raised the possibility that a reduced level of ABCC6 protein contributes to the mineralization phenotype of humans with β-thalassemia, although this needs further investigation.…”
Section: Is Pxe Pathology Related To Oxidative Stress?mentioning
confidence: 99%